Prosedur Pengajuan Akad Rahn Pada Emas Batangan Di PT Bank Syariah Mandiri Cabang Rawamangun - Nidaul Izzah; Savira Nurul Annisa (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2019)
The final report written based on observation in PT Sharia Bank Mandiri Rawamangun branch. Observation methods conducted with observations and interview related to convenant on gold bars. The purpose of this reservation is to know the filing procedures of convenant on gold bars in PT Sharia Bank Mandiri. To apply for gold pawn financing in PT Sharia Bank Mandiri Rawamangun branch, customer comes to the branch office to fill out the application form and attach some requirements like identity card, NPWP card if the financing is above 50 million, have a saving account and warranty of gold bars. In this case, so gold pawn financing can familiar in public especially the middle to lower society then need to socialization and promotion like opening outlets on campus, central business and shopping center.